ICT - Energy Concepts for Energy Efficiency and Sustainability - Fagas, Giorgos; Gammaitoni, Luca; Gallagher, John P.; Paul, Douglas J. (IntechOpen, 2017)
In a previous volume (ICT-Energy-Concepts Towards Zero-Power ICT; referenced below as Vol. 1), we addressed some of the fundamentals related to bridging the gap between the amount of energy required to operate portable/mobile ICT systems and the amount of energy available from ambient sources. The only viable solution appears to be to attack the gap from both sides, i.e. to reduce the amount of energy dissipated during computation and to improve the efficiency in energy-harvesting technologies. In this book, we build on those concepts and continue the discussion on energy efficiency and sustainability by addressing the minimisation of energy consumption at different levels across the ICT system stack, from hardware to software, as well as discussing energy consumption issues in high-performance computing (HPC), data centres and communication in sensor networks. This book was realised thanks to the contribution of the project 'Coordinating Research Efforts of the ICT-Energy Community' funded from the European Union under the Future and Emerging Technologies (FET) area of the Seventh Framework Programme for Research and Technological Development (grant agreement n. 611004).